Professional success and satisfaction in the career development: Gender patterns - Sanchez-García, Maria Fe; Suárez-Ortega, Magdalena (Revista de Investigación Educativa, 2021)
This paper examines a series of variables related to the profesional development of young and adult workers from a gender perspective. It analyses, within the Spanish context, how working women and men subjectively perceive their professional success, paying attention to the identification and following of gender patterns. Quantitative and qualitative methodologies are combined in a mixed approach that uses a questionnaire (given to a sample of 205 workers) and interviews (with a subsample of 32 individuals). Their results enable us to describe a marked duality in the perception of career progression, job satisfaction and achievement expectations in relation to gender but also age. The barriers perceived in professional development also present differentiated patterns. Practical implications are derived with a view to improve career guidance strategies for working women and men, taking this reality into account.